On-chip droplet characterisation using impedance-based measurement - Low, Jerome Fang Yao (2017)
This paper investigates an impedance-based on-chip droplet characterisation and the suitability for black silicon to be used as biological sensors. As black silicon is superhydrophobic, black silicon substrates can be used instead to reduce the “hugging” of the dispersed phase to the substrate’s surface. The use of black silicon substrates may even lead to decreased reaction times and higher sensitivity for the lab-on-chip devices that are currently using other substrates.